Soft Tissue Manipulation and Naprapathy: Origins and Current Practices - Miranda Budagher-Marshall; Dominique Alò (Tehran University of Medical Sciences, 2023)
Naprapathy is an integrative medicine therapy that can aide in decreasing medical costs by assisting in pain management and improving overall function in individuals experiencing musculoskeletal pain and dysfunction. Naprapathy was developed in 1907 by Oakley Smith. Naprapathy treats musculoskeletal pathologies by using connective tissue tension found within the vertebral column and peripheral joints with an emphasis on ligamentous tension. Current scientific studies have emphasized the role of fascia and its importance to manual medicine. Fascia has many properties including assisting in venous return, dissipation of tensional stress, pain, proprioception, and coordination of movement. Fascial restrictions occur when there is lack of glide between the fascial layers. These restrictions can be released with the utilization of different methods of fascial manipulation. Compared to other manual therapies, naprapathy has its own set of diagnostic tools and protocols emphasizing the treatment of fascial restrictions, stretching of buckled ligaments and tracing tension to the musculoskeletal system It includes within its scope of practice dietary counseling in conjunction with vitamin and mineral supplementation for assistance in decreasing pain and inflammation. Several organizations and schools throughout the U.S. and internationally promote the discipline of naprapathy with the goal of advancing the profession by preparing practitioners at the doctorate level, treating patients, and using evidence-based medicine providing support for the efficacy of naprapathy and its interventions.